Consumer Religiosity: Consequences for Consumer Activism in the United States - Swimberghe, Krist (Journal of business ethics, 2011)
In recent times, organizations have experienced consumer backlash as a result of decisions to support controversial causes. To date, little research has attempted to explain consumers’ negative response as a function of religion. This study addresses that gap in the literature and examines consumer religious commitment and Christian consumers’ conservative beliefs in the United States as motivating factors for consumer activist behavior and boycott participation. Findings from a national sample of 531 consumers suggest that consumers evaluate seller’s actions and form ethical judgments. These judgments are a major explanatory variable in consumers’ voice complaints, third-party complaint intentions, and boycott intentions.